Implementasi Hadits Nabi Sebagai Panduan Nilai-Nilai Ilahiah Dalam Pengembangan Manjemen Pendidikan Islam - Laksana, Inggil; Masdaudi, Muhammad Royan (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2025)
This study aims to explore the relevance and implementation of the hadiths of Prophet Muhammad (peace be upon him) as a guide to divine values in the development of Islamic education management. As one of the primary sources of Islamic teachings, hadiths contain various moral and ethical principles that can serve as guidelines in managing Islamic educational institutions. This research employs a library research method by analyzing classical and contemporary literature related to the Prophet’s hadiths, concepts of Islamic education management, and previous research findings. Data were obtained from collections of hadiths, books on Islamic education management, and relevant academic journals, then systematically analyzed to identify applicable divine values within the context of modern education. The results of the study indicate that the hadiths of the Prophet hold significant relevance in shaping the principles of Islamic education management, particularly in the aspects of justice, honesty, the importance of knowledge, social ethics, and exemplary leadership. The implementation of these values contributes to creating a fair, inclusive, and moral educational environment, while also strengthening students' character and educators' professionalism. Furthermore, the integration of hadith values into curricula, school culture, and social interactions within educational settings can enrich learning experiences and foster organizational culture aligned with Islamic values. This research recommends providing specialized training for educators and educational leaders to optimize the application of hadith values in the management of Islamic educational institutions.